Pengaruh Jarak Tanam terhadap Kecernaan In Vitro Bahan Kering dan Kecernaan Bahan Organik Serta TDN (Total Digestible Nutrient) Tanaman Indigofera Zollingeriana - Saununu, Beryl Gabriela Sofia; Nastiti, Herayanti Panca; Osa, Dominggus B. (Animal Agricultura, 2024)
The aim of this study was to determine the effect of plant spacing on the in-vitro digestibility of dry matter, organic matter and TDN (Total Digestible Nutrient) Indigofera zollingeriana plants. The method used in this study was an experimental trial method using a Completely Randomized Design (CRD) consisting of 4 treatments and 6 replicates with treatment arrangement, J1=1.0m×1.25m, J2=1.0m×1.0m, J3=1.0m×0.75m, J4=1.0m×0.5m. Data analysis using Analysis Of Varians (ANOVA). The variables measured were in vitro digestibility of dry matter, organic matter digestibility, and TDN. The variables measured were dry matter in-vitro digestibility, organic matter digestibility, and TDN. The results showed that plant spacing had no significant effect (P>0.05) on dry matter in-vitro digestibility, organic matter digestibility, and TDN for Indigofera zollingeriana. It was concluded that spacing had relatively the same effect on the in vitro digestibility of dry matter, organic matter and TDN of Indigofera zollingeriana plants.